RelB/p50 regulates TNF production in LPS-stimulated dendritic cells and macrophages - Gasparini, C; Foxwell, B; Feldmann, M (2013)
Dendritic cells (DCs) and macrophages are effective antigen-presenting cells, and DCs, once matured, have the ability to potently activate naïve T cells. While the canonical p65/p50 NF-κB pathway seems to have an important role during LPS-stimulation of these cells, the specific contribution of the non-canonical RelB/p50 subunits is not clear yet. We aimed to investigate the relevance of this pathway in DCs and macrophages by using replication-deficient adenoviruses overexpressing RelB and p50 subunits to test their effect on cytokine production. In both cells, after LPS treatment, overexpression of RelB and p50 inhibited the production of some pro-inflammatory cytokines e.g., TNF, but not of others e.g. IL6. Anti-inflammatory IL10 was not affected. Moreover, when overexpressing p50 alone, IL10 was increased in LPS-activated macrophages. We thus demonstrated that the dimer RelB/p50 rather than the p50/p50 complex inhibits TNF production in LPS-stimulated DCs and macrophages. This implies that the non-canonical RelB/p50 could modulate the canonical p65/p50 pathway. © 2013 Elsevier Ltd.